Study of the Drell-Yan process with the ATLAS detector at the LHC - Giuli, F (2018)
The Large Hadron Collider (LHC) at CERN, at which protons collide at unprecedented center of mass energies and very high instantaneous luminosity, gives unique possibilities for precise tests of the Standard Model and to search for new physics phenomena. A precise prediction of the processes at the LHC is essential and the knowledge of the parton density functions (PDFs) of the proton plays a key role in this. In this thesis, three analyses covering different aspects of the Drell-Yan process are presented.